Habitar Mundos: Ou como construir paisagens como espaços de pertencimento - Rigatti, André Luiz (Revista do Colóquio, 2021)
This essay seeks to build a reflection about the creation process of this artist / researcher around the practice of painting, its problematization and respective poetic and conceptual developments. It also aims to critically investigate the progress of artistic making as an academic investigation, in which the issue surrounding spatiality is one of the guides for both theoretical reflection and practical development. To inhabit worlds would mean, from this perspective, to consider how painting develops by questioning its space of materialization, as well as, a specific sense of space for its existence. As a starting point, its abstract state of spatiality is considered, which evokes meanings of landscape for its configuration and possible transformations throughout the process. Thus building a reflection where painting generates spaces of belonging, a metaphor for a space to be inhabited.
Keywords: Creation Process; Painting; Spatiality